Human Righteousness and Cruelty as Depicted in Anna Sewell’s Black Beauty - Tini Mogea (FKIP, Universitas Palangka Raya, 2022)
This research aims at revealing human righteousness and cruelty in Sewell’s Black Beauty. This study is regarded as qualitative research that pictures the data in the form of words and quotations. The writer collects and selects the data from the primary source, the novel itself, and the secondary source, which includes books explaining research, literature, and some other references that are relevant and support the analysis. In analyzing the data, the writer uses an objective approach that focuses on the work itself. The writer focuses on human characters in treating the animals. The result shows that humans have their own ways of treating horses. There are kind humans who treat them rightly, feed them properly, and are kind to them. But still, there are unkind humans who have bad tempers and treat these horses cruelly, torture them, and even hurt them in the name of fashion. Sometimes the horses meet kind masters and also bad masters, especially the main character in this story, Black Beauty. At the end of the story, he becomes a tough, handsome, and good horse and meets a kind master who treats the old beauty. Kindly and wisely.